BIAS GENDER KOREOGRAFER WANITA DALAM KARYA TARI - Bisri, Hasan (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
This study examines how the construction of gender roles in the world of dance artists, particularly female choreographer. The purpose of this study is to understand and explain: (1) the construction of gender roles that took place in the work of dance by female choreographer, and (2) gender bias that occurred in the work of dance by female choreographer. Qualitative method is employed in the study which is located in Semarang city. The subjects consisted of the female dance stylist (choreographer), dancers, musicians, and audiences. Data collection techniques used included interviews, questionnaires, observation, and documentation. Data analysis was done by developing case description, conducted through data reduction, categorization, and interpretation (verification/drawing conclusions). The result showed that the construction of gender roles in the process of dance works choreographed by woman happened in family and community setting. Objective reality that includes a variety of views, attitudes, behaviors, and meaning giving to the differentiation of the roles of men and women based on culture (nurture) contained in family environment plays a prominent position in role construction process among female dancer and choreographers. As for male dancers, the process of role construction went on within the setting of family and social environment of society. Gender bias that occurred in the construction of gender roles in this study is indicated by the existing presence of gender stereotype views among dancers, choreographers, audience, and dance lovers community. Kata kunci: kunstruksi, bias gender, proses karya tari